Interpersonal Communication Patterns of Parents and Children in Preventing the Spread of Hoax Information - Adhani, Abrar; Anshori, Akhyar; Nasution, Nurhasanah (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
The development of information currently circulating requires sorting and selecting actions for all information obtained to prevent hoax information. One of the people who must play a role is parents by providing an understanding of the importance of media literacy. This research aims to find out 1) the methods used by parents in supervising their children's use of gadgets and social media, and 2) the role of parents in carrying out media literacy in children so that they can minimize the negative impact usage of gadgets and social media. The research was conducted using a qualitative approach with data collection techniques through interviews with three informants who already have children in their teens, and each owns a cellular phone. The analysis uses interpersonal communication theory by DeVito, He highlights the importance of effective communication in relationship development, emphasizing that it occurs within specific cultural, social, and environmental contexts. The results were processed by reducing the data, presenting the data, and verifying the data. The research results found that parents' actions towards children in monitoring the use of cellphones and social media are not an act of distrust towards children, but rather an effort to provide literacy to children about the impact of incorrect information.